RBM8A Promotes Glioblastoma Growth and Invasion Through the Notch/STAT3 Pathway - Lin, Yan; Wei, Lei; Hu, Beiquan; Zhang, Jinyan; Wei, Jiazhang; Qian, Zhongrun; Zou, Donghua (Frontiers in Oncology, 2021)
Background: Glioblastoma (GBM) is a prevalent brain malignancy with an extremely poor prognosis, which is attributable to its invasive biological behavior. The RNA-binding motif protein 8A (RBM8A) has different effects on various human cancers. However, the role of RBM8A in GBM progression remains unclear. Methods: We investigated the expression levels of RBM8A in 94 GBM patients and explored the correlation between RBM8A expression and patient prognosis. Using in vitro and in vivo assays, combined with GBM sequencing data from the Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA), we examined whether and how RBM8A contributes to GBM progression. Results: RBM8A was up-regulated in GBM tissues, and its higher expression correlated with worse prognosis. Knockdown of RBM8A inhibited GBM progression and invasion ability both in vitro and in vivo. On the contrary, overexpression of RBM8A promoted GBM progression and invasion ability. Enrichment analysis of differentially expressed genes in GBM data identified the Notch1/STAT3 network as a potential downstream target of RBM8A, and this was supported by molecular docking studies. Furthermore, we demonstrated that RBM8A regulates the transcriptional activity of CBF1. The γ-secretase inhibitor DAPT significantly reversed RBM8A-enhanced GBM cell proliferation and invasion, and was associated with down-regulation of p-STAT3 and Notch1 protein. Finally, the gene set variance analysis score of genes involved in regulation of the Notch1/STAT3 network by RBM8A showed good diagnostic and prognostic value for GBM. Conclusions: RBM8A may promote GBM cell proliferation and migration by activating the Notch/STAT3 pathway in GBM cells, suggesting that RBM8A may serve as a potential therapeutic target for the treatment of GBM.